Impacts of Green Perception Benefits and Environmental Regulation Intensity on Farmers’ Agricultural Green Production Willingness: A New Perspective of Technology Acquisition - Mingyue Li; Pujie Zhao; Yu Sun (Agriculture)
Agricultural green production (AGP) is a key strategy for ensuring stable and sustainable grain production in developing countries. However, from the perspective of technology acquisition, research on farmers’ willingness to adopt AGP remains limited. Based on this, a survey was conducted on 862 households in major grain-producing counties in the Huang Huai Hai Plain of China with a reliable and effective response rate of 97.44%. The aim was to employ Probit and mediation models to empirically analyze the direct impacts of green perception benefits and environmental regulation intensity on farmers’ AGP willingness, and further examine the intrinsic mechanisms of technology acquisition. The results demonstrated that both green perception benefits and environmental regulation intensity significantly enhanced farmers’ willingness to engage in AGP, with green perception benefits having a greater influence. Among the two-dimensional variables, economic benefits had a stronger promoting effect than identity benefits, with a difference of 0.044 units, while subjective regulation intensity outperformed objective regulation intensity by 0.173 units. This suggested the need to strengthen the subjective impact of AGP policies in practice. Further analysis revealed that technology acquisition mediated 5.87% of the effect of green perception benefits on farmers’ AGP willingness, with acquisition evaluation having the greatest mediating effect, followed by acquisition quality and acquisition channels. However, although the overall environmental regulation intensity did not significantly impact farmers’ willingness to engage in AGP, its two-dimensional indicators played a mediating role to varying degrees. The findings in this study provide valuable empirical evidence for promoting AGP among grain producers, contributing to grain production security and the sustainable development of developing countries. Thus, implementing environmental regulatory policies tailored to local conditions, enhancing farmers’ economic awareness and sense of responsibility, and expanding farmers’ channels for technology acquisition are reasonable policy choices.